Synthesis of pyrazoline derivatives from the 1,3-dipolar cycloadditions using α,β-unsaturated cyclohexanone derivatives - Ziani, Nouara; Lamara, Kaddour; Sid, Assia; Willem, Quentin; Dassonneville, Benjamin; Demonceau, Albert (European Journal of Chemistry, 2013)
A series of 2-pyrazolines (3a-d) were obtained by reaction 1,3-dipolar cycloadditions of α,β-unsaturated cyclohexanone derivatives (2a-c) with hydrazine hydrate and 4-nitrophenylhydrazine in the presence of acetic acid and ethanol as solvents. The structures of the synthesized compounds were confirmed by spectroscopic methods; IR, 1H and 13C NMR.